Using interpersonal affect regulation in simulated healthcare consultations: an experimental investigation of self-control resource depletion - Martínez-Íñigo, David; Mercado, Francisco; Totterdell, Peter (Frontiers in Psychology, 2015)
Controlled Interpersonal Affect Regulation –the process of deliberately influencing the internal feeling states of others– occurs in a variety of interpersonal relationships and contexts. An incipient corpus of research shows that interpersonal affect regulation can be characterized as a goal-directed behaviour that uses self-control processes which, according to the strength model of self-regulation, consumes a limited resource that is also used by other self-control processes. Using interpersonal affect-improving and affect-worsening regulation strategies can increase agents´ resource depletion but there is reason to think that effects will partially rely on targets´ feedback in response to the regulation. Using a healthcare paradigm, an experiment was conducted to test the combined effects of interpersonal affect regulation use and patient feedback on healthcare workers’ resource depletion, measured as self-reported actual and expected emotional exhaustion, and persistence on a self-regulation task. Medical students (N = 78) were randomly assigned to a 2(interpersonal affect regulation: affect-worsening vs. affect-improving) x 2(patients’ feedback: positive vs. negative) factorial between-subjects design and given instructions to play the role of doctors in interactions with two professional actors trained to act as patients. Analysis of covariance showed that affect-worsening was more depleting than affect-improving for all measures, whereas the recovery effects of positive feedback varied depending on strategy type and measure. The findings confirm the characterization of interpersonal affect regulation as potentially depleting, but suggest that the correspondence between the agent´s strategy and the target´s response needs to be taken into consideration. Use of affect-improving and positive feedback showed positive effects on self-rated performance, indicating that interpersonal affect regulation is relevant for organizational as well as personal outcomes.